First report of MDR virulent Pseudomonas aeruginosa in apparently healthy Japanese quail (Coturnix japonica) in Bangladesh. - Alamgir Hasan; Md Tanjir Ahmmed; Bushra Benta Rahman Prapti; Aminur Rahman; Tasnim Islam; Chandra Shaker Chouhan; A K M Anisur Rahman; Mahbubul Pratik Siddique (PLoS ONE)
Pseudomonas aeruginosa (P. aeruginosa) is a major pathogen associated conditions like septicaemia, respiratory disorders, and diarrhoea in poultry, particularly in Japanese quail (Coturnix japonica). The infection causes huge economical losses due to its high transmissibility, mortality and zoonotic potential. This study aimed to isolate, identify, detect virulence genes, and profile multidrug resistance (MDR) of P. aeruginosa from Japanese quail. Oral and rectal swabs were collected from 110 apparently healthy quail birds across various districts in Bangladesh. Bacterial isolation and identification were performed using cultural, morphological, biochemical, and polymerase chain reaction (PCR) methods. Antibiotic susceptibility was assessed using the disc diffusion method, and virulence genes were detected through PCR. Multivariable logistic regression was used to identify risk factors for P. aeruginosa infection. Both conventional and PCR methods revealed that 25 (22.73%) of the quail birds were positive for P. aeruginosa. The results showed that quail birds in Narsingdi were five times more likely to harbor Pseudomonas species (OR: 5.02; 95% CI: 1.34-18.84) compared to those in Mymensingh Sadar. Additionally, quail birds younger than eight weeks had nearly six times higher odds (OR: 5.93; 95% CI: 1.96-17.91) of carrying Pseudomonas compared to older birds. Female quail birds had almost four times higher odds (OR: 3.77; 95% CI: 1.30-10.93) of harboring Pseudomonas species than males. All 25 P. aeruginosa isolates exhibited multi drug-resistance (MDR) patterns. Virulence gene analysis revealed the consistent presence of exoA and rhlR in all isolates, while exoS, exoY, rhlI, and rhlAB showed variable distribution. The high prevalence of MDR and virulent P. aeruginosa in apparently healthy quail birds particularly in Mymensingh and Dhaka divisions, highlights the urgent need for a comprehensive 'One Health' approach to proactively address and mitigate the potential risk this organism poses to both quail and human populations.